Investigating the nature and prevalence of mobile bullying in the rural Eastern Cape Province of South Africa - Mtshazi, Sive (Department of Information Systems, 2022)
Limited studies have examined mobile bullying in South African schools in general and in rural schools in particular. The focus on rural schools is important to our understanding of the nature and forms of bullying. Studies conducted in other parts of the world suggest that bullying differs among urban, suburban, and rural schools. Evidence from studies on physical violence suggests that violence also takes place in many rural schools. Since rural areas are reported to have the highest level of mobile phone usage in South Africa, it is possible that mobile bullying may be more predominant in the rural communities and its implications severe. Using a survey of 984 students, the present study investigated the nature of mobile bullying in 7 rural high schools of the Eastern Cape Province of South Africa. It sought to identify the factors that mainly predict this aggression and the data was analysed using quantitative methods. The findings show that males are more involved in mobile bullying than females. Gender, mobile victimization, frequent usage of the mobile phone and retaliation were the main predictors of mobile bullying. This study also revealed that the influence of anonymity of the bully on mobile bullying is not necessarily direct. This influence is moderated by other factors such as the safety risk and the economic environment of school.